Reservoir formation mechanism analysis and deep high-quality reservoir prediction in Yingcheng Formation in Longfengshan area of Songliao Basin, China - Yongmei Zhang; Xiaoqi Ding; Peng Yang; Yan Liu; Qi Jiang; Shaonan Zhang (Petroleum, 2016)
Although commercial gas flow was produced in several wells with recent years' exploration of Longfengshan area in Changling fault sag, the formation mechanism and controlling factors for high-quality reservoirs still remained undefined. Here, the Yingcheng tight gas reservoirs of Longfengshan area are used as an example to characterize high-quality reservoir formation mechanism and distribution rules. Based on the thin section, SEM, X-ray diffraction, computed tomography (CT) scanning, burial history, constant-rate mercury penetration and physical properties testing, formation mechanism and controlling factors for high-quality reservoirs were analyzed. Results show the following characteristics. First, the reservoir is dominated by chlorite and laumontite cements, and compaction is the most important factor to control reservoir physical properties. According to this, the reservoir can be divided into compacted tight sandstones, chlorite-cemented sandstones and laumontite-cemented sandstones. Second, the high-quality reservoirs are formed due to early extensive laumontite precipitation and the later dissolution of laumontite by organic acid. Meanwhile, it is found that the distribution of cementation and dissolution exhibits some regulations in sedimentary facies, and the distribution is mainly effected and controlled by the lake water and charging of fresh water. Besides, the distribution model of various types of sandstones was established. Studies over diagenesis and sedimentary facies reveal that the high-quality laumontite-cemented sandstones exist in the outside subaqueous fan-delta of the deep sag in Longfengshan area. These findings have been validated by recent exploration wells which obtained high industrial gas flow.